Mobile Genetic Elements in the Human MGMT Gene and their Regulatory Potential - Pidpala, O. V.; Lukash, L. L. (Recent Developments in Medicine and Medical Research Vol. 1, 2021)
Mobile genetic elements (MGEs) make up a large part of the DNA of eukaryotes, in particular, almost 45 % of the human genome. Numerous data show the diverse role of these elements in the genome - from plasticity factors to mutability or stability. They discuss their role in the evolution of genomes and the evolution of gene regulation. The purpose of this work was to investigate the distribution of MGEs in human MGMT gene and their regulatory potential. It is shown that in the human MGMT gene MGEs are present both in the intron sequences and in the promoter region. In the intron sequences, MGEs form composite cluster structures that are the source of various regulatory sequences and have the potential to form alternative promoters. In the promoter region, three sequences of MGEs were identified: two LTR-repeats and a fragment of the DNA-transposon. The MGEs fragments in the promoter region of human MGMT also enriched with potential cis-regulatory sequences that may be involved in the regulation of this gene.